Being helpful to other‐gender peers: School‐age children's gender‐based intergroup prosocial behaviour. (24th June 2022) - Xiao, Sonya Xinyue; Martin, Carol Lynn; Spinrad, Tracy L.; Eisenberg, Nancy; DeLay, Dawn; Hanish, Laura D.; Fabes, Richard A.; Oswalt, Krista
Abstract: Promoting prosocial behaviour towards those who are dissimilar from oneself is an urgent contemporary issue. Because children spend much time in same‐gender relationships, promoting other‐gender prosociality could help them develop more inclusive relationships. Our goals were to better understand the development of school‐age children's intergroup prosocial behavior and the extent to which elementary school‐age children consider their own and the recipient's gender in prosocial behaviour. Participants included 515 3rd, 4th and 5th graders (263, 51.1% boys, M ageinyears = 9.08, SD = 1.00) surveyed in the fall (T1) and spring (T2). We assessed children's prosociality using peer nominations. Children became more prosocial toward same‐gender peers over time but prosocial behavior toward other‐gender peers remained stable. We found that gender mattered: Children showed an ingroup bias in prosociality favouring members of their own‐gender group. Having other‐gender friendships positively predicted children's prosocial behaviour towards other‐gender peers over time. Children's felt similarity to other‐gender peers was not directly, but indirectly, related to more prosocial behaviour toward other‐gender peers. Findings shed light on potential pathways to fostering school‐age children's intergroup prosocial behaviors.